2016
DOI: 10.1172/jci.insight.88907
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced protective antibody to a mutant meningococcal factor H-binding protein with low-factor H binding

Abstract: Meningococcal factor H-binding protein (FHbp) is an antigen in 2 serogroup B meningococcal vaccines. FHbp specifically binds human and some nonhuman primate complement FH. To investigate the effect of binding of FH to FHbp on protective antibody responses, we immunized infant rhesus macaques with either a control recombinant FHbp antigen that bound macaque FH or a mutant antigen with 2 amino acid substitutions and >250-fold lower affinity for FH. The mutant antigen elicited 3-fold higher serum IgG anti-FHbp ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 55 publications
(89 reference statements)
0
28
0
Order By: Relevance
“…Eliminating the ability of CspZ to bind FH exposes the FH-binding site and, therefore, may increase the ability of the epitopes close to/within this site to induce bactericidal antibodies. In fact, immunization with point mutants of a Neisseria meningitidis FH-binding protein fHbp with reduced FH-binding activity induces greater levels of bactericidal antibodies in vaccinated human FH-transgenic mice and in non-human primates than immunization with wild-type fHbp ( 19 , 42 45 ). This reduction in immunogenicity as a result of binding to host proteins thus is not restricted to FH-binding molecules ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Eliminating the ability of CspZ to bind FH exposes the FH-binding site and, therefore, may increase the ability of the epitopes close to/within this site to induce bactericidal antibodies. In fact, immunization with point mutants of a Neisseria meningitidis FH-binding protein fHbp with reduced FH-binding activity induces greater levels of bactericidal antibodies in vaccinated human FH-transgenic mice and in non-human primates than immunization with wild-type fHbp ( 19 , 42 45 ). This reduction in immunogenicity as a result of binding to host proteins thus is not restricted to FH-binding molecules ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, other reports have shown that the binding of host molecules to vaccine targets can result in the induction of the antibodies directed against parts of the vaccine target that are not involved in the binding to the complement regulatory protein. This phenomenon can be overcome by the use of mutated bacterial proteins that are no longer able to bind their host target protein (Rossi et al, 2013; Zariri et al, 2013; Costa et al, 2014; Granoff et al, 2016). Therefore, the use of mutated complement evasion molecules that no longer bind to their host target proteins should be considered in the design of microbial vaccines that aim to elicit antibodies that block binding of the host complement regulator to the pathogen.…”
Section: Complement Evasion Molecules As Vaccine Targetsmentioning
confidence: 99%
“…Some antibodies also inhibit the binding of human complement factor H (fH) to the bacteria, rendering them more susceptible to complement 12 . While some antibodies to fHbp elicited in mice inhibited the binding of fH to the bacterial surface 12 , 13 , the antibodies elicited in rhesus macaques 14 , 15 or humans 16 generally did not inhibit binding of fH. This difference may result from the inability of murine fH to bind fHbp 16 , in contrast to human fH that binds fHbp, such that the dynamics of epitope exposure, dependent on fH binding, are likely different when immunizing mice and humans.…”
Section: Introductionmentioning
confidence: 97%